Dual‐role FilmArray® diagnostics for high‐impact viral diseases. Issue 3 (March 2016) - Dorsch, M; Meehan, B; Michalski, WP; Heine, HG; Foord, AJ; Carlile, G; Wang, J; McCullough, S; Zuelke, K
Abstract : In this study, we explored the potential utility of the human‐focused FilmArray® Respiratory Panel for the diagnosis of a broad range of influenza viruses of veterinary concern as compared with the standard portfolio of recommended TaqMan®‐based diagnostic tests. In addition, we discuss some potential operational advantages associated with the use of such integrated sample extraction, amplification and analysis devices in the context of a future long‐term, dual‐role strategy for the detection of emergency diseases of both human and veterinary concern.